Characteristics of Mid-Term Post-Intensive Care Syndrome in Patients Attending a Follow-Up Clinic: A Prospective Comparison Between COVID-19 and Non-COVID-19 Survivors. (18th January 2023) - Rousseau, Anne-Françoise; Colson, Camille; Minguet, Pauline; Kellens, Isabelle; Collard, Maxine; Vancraybex, Camille; Guiot, Julien; Lambermont, Bernard; Misset, Benoit
Abstract : IMPORTANCE: At present, it is not clear if critically ill COVID-19 survivors have different needs in terms of follow-up compared with other critically ill survivors, and thus if duplicated post-ICU trajectories are mandatory. OBJECTIVES: To compare the post-intensive care syndrome (PICS) of COVID-19 acute respiratory distress syndrome and non-COVID-19 (NC) survivors referred to a follow-up clinic at 3 months (M3) after ICU discharge. DESIGN, SETTING, AND PARTICIPANTS: Adults who survived an ICU stay greater than or equal to 7 days and attended the M3 consultation were included in this observational study performed in a post-ICU follow-up clinic of a single tertiary hospital. MAIN OUTCOMES AND MEASURES: Patients underwent a standardized assessment, addressing health-related quality of life (3-level version of EQ-5D), sleep disorders (Pittsburgh Sleep Quality Index [PSQI]), physical status (Barthel index, handgrip and quadriceps strengths), mental health disorders (Hospital Anxiety and Depression Scale and Impact of Event Scale-Revised [IES-R]), and cognitive impairment (Montreal Cognitive Assessment [MoCA]). RESULTS: A total of 143 survivors (86 COVID and 57 NC) attended the M3 consultation. Their median age and severity scores were similar. NC patients had a shorter ICU stay (10 d [8–17.2 d]) compared with COVID group (18 d [10.8–30 d]) ( p = 0.001). M3 outcomes were similar in the two groups, except for a higher PSQI ( p = 0.038) in the COVID group (6 [3–9.5]) versus NC group (4 [2–7]), and a slightly lower Barthel index in the NC group (100 [100–100]) than in the COVID group (100 [85–100]) ( p = 0.026). However, the proportion of patients with abnormal values at each score was similar in the two groups. Health-related quality of life was similar in the two groups. The three MoCA (≥ 26), IES-R (<33), and Barthel (=100) were normal in 58 of 143 patients (40.6%). In contrast, 68.5% (98/143) had not returned to their baseline level of daily activities. CONCLUSIONS AND RELEVANCE: In our follow-up clinic at 3 months after discharge, the proportion of patients presenting alterations in the main PICS domains was similar whether they survived a COVID-19 or another critical illness, despite longer ICU stay in COVID group. Cognition and sleep were the two most affected PICS domains.